(untitled) (Patan Prospective Journal, 2023)
International security is a comprehensive concept. There is a change in the dynamics of international security in the international arena. In the present context, the world has been shifting from unipolar to multipolar. The rise of China and the latest Russian attack on Ukraine have changed previous paradigms and parameters of international and regional security. After the proposed Belt and Road Initiate (BRI) by Chinese President Xi Jinping in 2013, the United States and its alliance proposed the Indo-pacific strategy (IPS) to counter the BRI. This article aims to give answer how and why IPS is crucial for international security, South Asian regional security and national security of Nepal. The objectives of this article are to analyze the security challenges created by IPS in international arena, to assess the security threat created by IPS in South Asian region, and to explore how Nepal can resolve and minimize a threat created by IPS and protect and promote its national security regarding IPS. In the context of South Asia, India is also involved in IPS. India is the dominant power in South Asia, so the active involvement of India in IPS also creates a threat to the regional security of South Asia. Nepal has to be conscious of the security aspect while cooperating with China, India, and other countries. Nepal is sensitive in terms of geopolitical, geo-strategic, and geo-economic aspects. The immediate neighbors’ China and India have been emerging as new great powers of the world. On the other hand, other great powers in the world also have prioritized Nepal strategically. So, Nepal has to continue its non-alignment trend and focus on its economic development and prosperity.